2008
DOI: 10.1111/j.1540-8167.2008.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Atrial Fibrillation Termination During Ablation Guided by Automated Detection of Fractionated Electrograms

Abstract: Ablation guided by automated detection of CFAE proved feasible, and was associated with a high AF termination rate in paroxysmal, but not persistent AF. As an adjunct to conventional techniques, it was associated with excellent long-term single procedure outcomes in both groups. Criteria for identifying optimal CFAE sites for ablation, and selection of patients most likely to benefit, require additional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 48 publications
9
93
1
Order By: Relevance
“…However, circumferential antral PV isolation, particularly if it is combined with additional modification of AF substrate, whether by the linear LA ablation and/or CFAE ablation, may lead to the occurrence of atrial tachycardia in 7.6%-44% of patients [24,42,54,[194][195][196]. After usage of similar ablative strategy (CFAE + PVI), post-procedural incidence of atrial tachycardia was remarkably higher after the ablation of persistent AF than after the ablation of paroxysmal AF (20.0% vs. 2.4%) [197].…”
Section: Phrenic Nerve Injurymentioning
confidence: 97%
“…However, circumferential antral PV isolation, particularly if it is combined with additional modification of AF substrate, whether by the linear LA ablation and/or CFAE ablation, may lead to the occurrence of atrial tachycardia in 7.6%-44% of patients [24,42,54,[194][195][196]. After usage of similar ablative strategy (CFAE + PVI), post-procedural incidence of atrial tachycardia was remarkably higher after the ablation of persistent AF than after the ablation of paroxysmal AF (20.0% vs. 2.4%) [197].…”
Section: Phrenic Nerve Injurymentioning
confidence: 97%
“…The highest efficacy reported by Porter and colleagues 33 was associated with one of the first attempts to objectively quantify (CARTO; Biosense Webster) and target CFAE in addition to conventional ablation. The algorithms yielded primary CFAE sites in an average 24% of the atrium, which were accordingly ablated.…”
Section: Cfae As An Adjunct To Conventional Approachesmentioning
confidence: 99%
“…Only two studies in this review objectively reported this statistic 19,33 . Another four other studies 7,13,24,28 have presumably followed all of their patients for at least 12 months given their mean and standard deviation; albeit none of these objectively stated this fact.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICL, ACI and SCI, as defined by CARTO, were calculated offline with a validated (100% agreement) MATLAB algorithm [4]. CFAE classification was performed by NavX and CARTO using their default clinical thresholds (CFEMean ≤ 120 ms; ICL ≥ 7) [8]. Primary and complementary indices from each system were optimized to reduce the differences in CFAE detection between them using receiver operating characteristic (ROC) curves.…”
Section: Automated Cfae Classificationmentioning
confidence: 99%